Clinical features, therapeutic outcomes, and recovery period of long COVID. Issue 1 (2nd December 2022) - Takakura, Kazuki; Suka, Machi; Kajihara, Mikio; Koido, Shigeo
Abstract: To characterize the clinical features of long COVID, 286 patients who received care in our outpatient clinic for long COVID from May to December 2021 were surveyed. The recovery periods of each symptom and the key factors contributing to early recovery were statistically analysed. The median age of the patients was 35.8 years, with 137 men and 149 women. The median number of symptoms was 2.8. The most frequent symptoms were respiratory manifestations (52.1%), followed by fatigue (51.4%). Respiratory symptoms, fatigue, and headache/arthralgia were major complaints in the initial phase, whereas hair loss was a major complaint in the late phase, suggesting that the chief complaint of patients with long COVID may vary temporally. The best treatment outcome was observed for pulmonary symptoms, and hair loss had the worst outcome. COVID‐19 severity, the number of manifestations, and the delay in starting treatment exerted a negative effect on the recovery period of long COVID. In addition, the smoking habit was an independent risk factor for slowing the recovery period from long COVID. This study provides insights into the clinical course of each manifestation and therapeutic options with a more certain future of long COVID to meet the unmet medical needs.